ANALISIS PENGARUH KUALITAS PRODUK, HARGA, DAN ULASAN PRODUK TERHADAP KEPUASAN KONSUMEN DALAM BELANJA ONLINE PRODUK SKINCARE HALAL Y.O.U (STUDI KASUS DI KALANGAN GENERASI Z KOTA BENGKULU) - Vanda Ibra Julika (JSE: Jurnal Sharia Economica, 2026)
This study aims to analyze the effect of product quality, price, and product reviews on consumer satisfaction in online shopping of halal skincare products Y.O.U among Generation Z in Bengkulu City. The rapid growth of digital technology has significantly influenced consumer behavior, particularly among Generation Z who actively engage in online shopping. This research uses a quantitative approach with data collected through questionnaires distributed to 100 respondents selected using purposive sampling. Data analysis techniques include validity and reliability tests, classical assumption tests, and multiple linear regression analysis using SPSS. The results show that product quality, price, and product reviews have a positive and significant effect on consumer satisfaction, both partially and simultaneously. Product quality is the most dominant variable affecting consumer satisfaction. These findings provide insights for businesses in developing effective digital marketing strategies in the halal skincare industry.